Navigating Challenges in Teaching Critical Thinking: A Study of Indonesian EFL Pre-Service Teachers’ Practicum - Asfiranti, Fifi; Fatoni, Mohammad; Verina Widya Putri, Nanin; Saeed, Sameerah T (English Department, Universitas Negeri Surabaya, 2025)
Applying critical thinking is the ability to actively analyze, assess and understand information in depth before making a decision or concluding something. Researchers conducted this research on two English language education students at Nahdlatul Ulama Sunan Giri University to find out what obstacles and efforts were applied when teaching in the classroom. This research uses a qualitative approach through semi-structured interviews. Based on the research results, there are eight obstacles faced by teachers, namely: traditional teaching methods, time constraints, assessment challenges, teacher training, disciplinary disorders, resistance to change, limited resources, and cultural and social factors. All of these obstacles have been overcome well, namely by using various efforts such as argument mapping, analyzing texts and sources, using real-world examples, encouraging collaborative learning, building relationships, providing clear instructions, encouraging inquiry-based learning, demonstrating thinking processes, improve academic achievement, and problem-solving skills. Recommendations for future researchers are to develop this research by using comparative classes and expanding the scope of the research and further researchers can develop it by using more research instruments to further strengthen the results applying.